Pengaruh Motivasi Terhadap Kinerja Karyawan PT. Fiber Networks Indonesia Tanjung Barat - Firmansyah, Alan; Evitha, Yuli; Novita Sari, Sukarni (JAMBIS : Jurnal Administrasi Bisnis, 2024)
The importance of employee performance is often a problem that needs to be addressed and he carries out the work to achieve these work results. The purpose of this study was to determine how much motivation affects employee performance at PT Fiber Networks Indonesia in Tanjung Barat and also what variables are contained in this study This type of research uses quantitative research. The quantitative approach is a research method based on the philosophy of potivism, used to research on certain populations or samples. by using 2 variables between variable X (Motivation) and also variable Y (Employee performance). Based on the results of the analysis and discussion of the data that has been described, there are conclusions that can be drawn from research on the effect of motivation on the performance of Fiber Network Indonesia Tanjung Barat employees, namely the variable influence of motivation (X) has a significant and positive effect on the employee performance variable (Y). This can be seen from the results of the T test where the value is 13.487 t in the table of 1.98667 and a significance value of 0.000 0.05, so it can be concluded that the variable influence of motivation (X) has a significant effect on the performance variable performance employeesolved by the company to achieve its goals. Employee performance not only refers to the work results that a person achieves when carrying out the work assigned to him, but also how.